Nickel oxide catalytic sheet, method for obtaining it and use thereof
By dispersing non-stoichiometric nickel oxide in the organic matrix to form a catalytic film supported on the substrate, the existing catalyst materials are solved, and the high-efficiency and low-cost water oxidation reaction is achieved, and H2 is improved. yield.
Patent Information
- Application Number
- CN202080044720.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-06-19
- Filing Date
- 2020-06-16
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-06-16
AI Technical Summary
In the existing water electrolysis technology, catalyst materials such as terpine oxide and ruthenium oxide are scarce and high costs, which limit the application on industrial scale. The manufacturing process of electrode materials is complex and costly, making it difficult to achieve economical large-scale production.
A catalytic film based on nickel oxide was developed, which was formed by dispersing non-stoichiometric nickel oxide in an organic matrix to form a catalytic film supported on the substrate, and was manufactured using low-cost wet deposition technology, with good catalytic characteristics and reduction. thickness.
Achieving efficient catalytic water oxidation reaction at low cost and low technical complexity, improving the yield of H2 generation, reducing the cost of catalyst materials, and providing a viable alternative for the production of clean energy.
Smart Images

Figure CN114007740B_ABST
Abstract
Description
[0001] The present invention belongs to the field of catalysts. In particular, the present invention relates to an improved catalytic membrane based on nickel oxide.
[0002] The catalytic membrane of the present invention is provided with an inorganic portion including non-stoichiometric nickel oxide dispersed in an organic portion supporting non-stoichiometric nickel oxide, and the catalytic membrane is supported on a substrate. Background Art
[0003] There is an increasing demand for clean energy generated from renewable sources. The development of clean energy is essential to mitigate climate change and limit its most destructive effects. One of the sources is H2 generated from the hydrolysis of water. Using H2 as a fuel to generate electricity in fuel cells is one of the most promising solutions, as it is a clean energy source, since its combustion generates H2O as a result of the reaction.
[0004] The hydrolysis of water is an endothermic process that requires very high temperatures, about 220 °C, for the reaction to occur spontaneously. An alternative is to hydrolyze water at room temperature by electrochemical methods. In this process, the following reactions occur:
[0005] H2O(l)→H2(g)+O2(g) hydrolysis
[0006] 2H + (aqueous solution)+2e - →H2(g) reduction in cathode (water reduction)
[0007] 2H2O(l)→O2(g)+4H + (Aqueous solution) + 4e - Oxidation in the anode (water oxidation)
[0008] The electrochemical splitting of water (electrolysis) is carried out with the aid of a direct current applied between two electrodes (anode and cathode). Thus, the reduction of water takes place in the cathode to produce H2, and the oxidation of water takes place in the anode to produce O2. However, the electrolysis of water requires a large amount of additional energy in the form of an overpotential relative to the overpotential theoretically required to carry it out (which is +1.23 V), because, as in any chemical reaction, the activation energy of the reaction needs to be overcome in order for it to occur. Catalysts are used to reduce the overpotential, because they significantly reduce the activation energy.
[0009] Among the existing materials used as selective electrodes for water oxidation, iridium oxide (IrO2) and ruthenium oxide (RuO2) are the electrocatalysts known to date with the best results. These electrocatalysts can also be used for water reduction. However, due to their scarcity, the high cost of Ru and Ir is one of the main factors limiting their implementation on an industrial scale.
[0010] Therefore, since both Ir and Ru are rare and expensive metals, it is necessary to develop new catalysts based on metals that are more abundant in the earth's crust and therefore more economical. The feasibility of obtaining clean energy in this way depends, in addition to the use of low-cost materials, on the ability to make catalysts from these materials with the aid of low-cost technologies and to produce H2 with improved yields.
[0011] Despite the great potential of the use of photoelectrochemistry in hydrogen production, it has not been possible so far to develop applications that could compete economically with conventional processes such as methane reforming (which allow hydrogen to be obtained at a lower cost, albeit with a significant carbon footprint that must be eliminated).
[0012] On the other hand, catalysts based on solid metal oxides such as CoPi, Co-Bi, CoOx, MnOx and NiOx are known. However, most of these oxides are deposited by chemical or electrochemical methods, by physical methods such as sputtering and by photochemical deposition methods.
[0013] Patent CN103974769 discloses obtaining metal oxides for catalytic purposes. However, the technique used, called photochemical metal organic deposition (PMOD), requires the use of ultraviolet (UV) radiation. In particular, a precursor is deposited and then irradiated with UV light until all organic materials decompose and form a metal in a metallic state, which is then oxidized using high temperatures. In addition to irradiating with UV light and using high temperatures to form the metal oxide and eliminate any organic residues initially present, the technique requires several steps.
[0014] In addition, patent JP2015049973 discloses the synthesis of Ni(0) nanoparticles (nickel 0 in a metallic state) from Ni(+2). After the reaction, the Ni(0) nanoparticles are deposited on the electrode.
[0015] Ehsani, A. et al., "Electrosynthesis of polypyrrole composite film and electrocatalytic oxidation of ethanol", ELECTROCHEMISTRY ACT, Vol. 71, pages 128-133, describe a catalytic sheet of nickel oxide comprising a dispersed polymerization Non-stoichiometric and crystalline nickel oxide in the oxidation states Ni2+ and Ni3+ (NiO2 and NiOOH) in an organic matrix (polypyrrole), supported on a substrate (graphite).
[0016] At the technical level, in order to promote alternative technologies based on the use of renewable energy, such as photoelectrocatalysis, it is necessary to reduce both the cost of the materials used and the cost of the manufacturing process of the devices for generating H2. In addition, continuous improvement of the H2 generation yield is necessary.
[0017] Recently, since these electrodes limit the increase in the yield of water hydrolysis reactions, studies have been conducted to obtain electrodes for O2 generation. This is because the water oxidation reaction is more difficult because there are more electrons than the water reduction reaction (2 electrons and 2H + ) More matter (4 electrons and 4H + ). This means that in the anode, the existing overpotential is very low, while in the cathode, a high overpotential exists due to the higher activation energy of the reaction. Therefore, there are large kinetic limitations on the electrochemical reaction for oxygen generation, limiting the effectiveness of water splitting by electrocatalysis.
[0018] Therefore, there is a need to provide improved catalysts based on metal oxides that are abundant in the earth's crust, which can be manufactured by low-cost techniques and can be used to oxidize water to O2 in good yields.
[0019] There are many research works on photocatalytic properties, among which broadband semiconductors are mainly used, mainly titanium oxide and zinc oxide.
[0020] Therefore, there is also a need to develop new and improved catalysts for decomposing pollutants present mainly in water, but also in air, with industrially applicable manufacturing procedures. Summary of the invention
[0021] With the catalytic membrane of the present invention, at least one of the above-mentioned disadvantages can be solved, with other advantages to be described.
[0022] In a first aspect, the present invention provides a nickel oxide catalytic film, characterized in that it comprises Ni in an oxidized state dispersed in an organic matrix. 2+ and Ni 3+ The catalytic film is supported on a substrate.
[0023] The catalytic film includes a non-stoichiometric nickel oxide containing a mixture of Ni(II) and Ni(III).
[0024] Advantageously, the presence of Ni(II) and Ni(III) in the catalytic film surprisingly improves the catalytic properties of an electrode comprising it relative to an electrode comprising Ni(0).
[0025] The catalytic membrane of the present invention comprises an organic portion as a support matrix for the non-stoichiometric nickel oxide, representing at least 10% by weight of the total weight of the catalytic membrane. The organic portion may represent a value of about 15-30%.
[0026] The authors of the present invention have discovered that the presence of a certain amount of organic material provides porosity to the catalytic membrane, which unexpectedly improves its catalytic properties.
[0027] The organic matrix may be formed of at least one organic compound selected from the group consisting of alkoxides, acetates, amines, and / or derivatives of any one thereof.
[0028] Therefore, the catalytic membrane of the present invention is a viable alternative for the oxidation of water to O2, with good yields, low cost of materials used to obtain the catalyst and ease of manufacture using low-cost technology, as will be described below.
[0029] Still another object of the present invention is to provide a catalytic membrane having improved catalytic properties, having a reduced thickness.
[0030] The catalytic membrane of the invention may have a thickness of less than 10 μm, preferably comprised between 20 and 600 nm, even more preferably comprised between 50 and 300 nm.
[0031] The catalytic membrane of the invention having good catalytic properties and reduced thickness can be obtained in the presence of an organic moiety.In the present invention, the thickness values given above refer to the layer thickness of the catalytic membrane supported on a substrate, excluding the substrate thickness.
[0032] The catalytic film may be formed of one or more layers, each layer forming a catalytic film supported on a substrate. These layers may be the same or different. The same or different in the present invention is understood to mean the same or different composition, which is understood to mean Ni 2+ and / or Ni 3+ Variations in the concentration of oxides and / or organic materials, and even variations in the percentage of organic material present in the organic portion of the catalytic membrane.
[0033] The catalytic film may further include metal nanoparticles and / or metal oxide nanoparticles. These metal nanoparticles and / or metal oxide nanoparticles are dispersed in an organic part that serves as a support matrix for these nanoparticles.
[0034] Nanoparticles are formed by salts and / or oxides of metals other than nickel, such as salts and / or oxides of Ag, Au, Ru, Ir, Pd, Pt, Re, Co, Fe, Os, Rh, Mo, V, which are added in solution and during the process of obtaining the catalytic film, together with oxides of Ni(II) and Ni(III), are used to form nanocomposites dispersed in an organic matrix. These nanocomposites may include mixed oxides.
[0035] Advantageously, the presence of such metal nanoparticles and / or metal oxides provides a catalytic membrane with greater versatility of application.Thus, the catalytic membrane according to the first aspect of the invention also provides a multifunctional catalytic membrane allowing optimization of its catalytic properties by incorporation of co-catalysts.
[0036] The structure and morphology of the catalyst film of the present invention make it possible to use a substrate of insulating material, conductive material or electric semiconductor material and even organic material. Similarly, the substrate can be a flexible, rigid or semi-rigid material. The substrate can also be transparent or opaque.
[0037] Among the materials of the substrate, the following can be cited as non-limiting examples of the present invention: transparent materials such as ITO and FTO on glass; rigid or semi-rigid materials, such as thin sheets of nickel, aluminum, steel or other metal carriers, and foams or fiber papers of metals such as nickel, and other types of rigid substrates such as flexible glassy carbon such as ITO, FTO, and metals such as Au, Pt deposited on polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polypropylene (PP), polyethylene (PE), polyimide (Kapton tape); organic materials such as cellulose.
[0038] In one embodiment, the catalytic membrane of the present invention supported on a substrate is an electrode.
[0039] In a second aspect, the present invention provides a method for obtaining a catalytic membrane according to the first aspect of the present invention.
[0040] The method for obtaining the catalytic film defined in the first aspect of the present invention is carried out on a substrate in a wet process as follows:
[0041] i) preparing a nickel oxide precursor solution;
[0042] ii) depositing the prepared solution on the substrate;
[0043] iii) solidifying the solution deposited on the substrate to obtain the nickel oxide catalytic film;
[0044] And it is characterized in that the method comprises:
[0045] In step i)
[0046] a)-selecting an organic counter ion nickel salt;
[0047] b) - dissolving the salt in a non-aqueous solvent of glycol ethers, glycol ether acetates and derivatives thereof in the presence of an amino alcohol chelating agent to obtain a solution of the nickel salt;
[0048] c) - heating the solution to a temperature between 20 and 200° C. and maintaining the solution at a constant temperature for a certain period of time under stirring to obtain an aged solution;
[0049] In step ii)
[0050] d) - depositing the aged solution on the substrate by conventional wet deposition techniques to obtain a wet film; and
[0051] In step iii)
[0052] e) - curing said aged solution deposited on said substrate at a temperature between room temperature and 200° C.,
[0053] The catalytic film is formed on the substrate, wherein the catalytic film includes Ni in an oxidized state dispersed in the organic matrix. 2+ and Ni 3+ The non-stoichiometric and crystalline nickel oxide film.
[0054] The method defined herein allows Ni(II) to be deposited directly on the electrode without prior reaction, which means greater simplicity and ease of use of any type of deposition method. The purpose of the method is not to generate Ni(0), but to generate a non-stoichiometric nickel oxide comprising a mixture of Ni(II) and Ni(III), these oxidation states being the reason for improving the catalytic properties of the membrane relative to the membrane or the membrane of the prior art with nickel in the oxidation state Ni(0).
[0055] Advantageously, the catalytic film of the present invention can be wet-coated on a substrate using a variety of deposition techniques [steps ii)-d]. Conventional techniques available to those skilled in the art may include spin coating, spray coating, dip coating or Dr. Blade. Likewise, it is compatible with roll-to-roll and inkjet printing, screen coating and flexographic printing techniques.
[0056] In step i)-a), the organic counter ion is selected from one of the following: acetate, formate, oxalate, carbonate, octanoyl glycolate, terephthalate, acetylacetonate, hexafluoroacetylacetonatoethylhexanoate, methoxyethanol, and sulfamate.
[0057] In steps i)-b), preferably the dissolved nickel salt is present in a concentration equal to or greater than 0.05 M. Preferably greater than 0.1M.
[0058] The non-aqueous solvent of glycol ether, glycol ether acetate and its derivative has the function of dissolving and stabilizing nickel salt.
[0059] Preferably, the non-aqueous solvent is selected from 2-methoxyethanol, 2-ethoxyethanol, 2-butoxyethanol, 2-(2-ethoxy-ethoxy)ethanol, 2-propoxyethanol, 2-isopropoxyethanol, 2-benzyloxyethanol, 2-(2-methoxyethoxy)ethanol, 2-(2-butoxyethoxy)ethanol and derivatives or mixtures thereof.
[0060] The amino alcohol chelating agent has the function of increasing the solubility and stability of the nickel salt in the solvent. Especially at high nickel concentrations, the lack of amino alcohol chelating agent in the solution causes the hydrolysis of the nickel salt and they precipitate in the form of gel.
[0061] Preferably, the amino alcohol chelating agent is selected from monoethanolamine (MEA), diethanolamine (DEA), triethanolamine (TEA) and derivatives or mixtures thereof.
[0062] In steps i)-c), the solution is preferably heated to a temperature comprised between 50-100°C, more preferably between 40-80°C.
[0063] In this step i)-c), the solution is aged so as to assume a viscosity comprised between 1.5 and 1,000 mPa·s, preferably between 1.5 and 100 mPa·s, measured by rotational viscometry at room temperature with a solution volume of 15 mL.
[0064] In steps iii) to e), the curing of the aged solution deposited on the substrate is preferably carried out at a temperature between room temperature and 100° C. During this heating, the solvent is removed. In the present invention, ambient temperature is understood to mean a temperature of 22-24° C. at atmospheric pressure.
[0065] Preferably, the temperature of the first curing is selected based on the volatility value of the organic compound present in the matrix so that the curing temperature does not completely remove the organic material; in this way, the catalytic film includes an organic portion that is partially responsible for improving the catalytic properties of the catalytic film of the invention. As a general rule, when the organic compound has a lower volatility, the curing is carried out at a higher temperature, and vice versa.
[0066] In an embodiment of the present invention, the method according to the second aspect of the present invention further comprises:
[0067] In steps i)-b)
[0068] - adding a previously prepared solution of one or more metal salts and / or metal oxides to the nickel solution; and,
[0069] In steps iii)-e)
[0070] - performing a second curing of the aged solution deposited on the substrate, wherein the second curing is performed at a higher temperature than the temperature of the first curing,
[0071] The remaining steps are performed as defined above in the method for obtaining the catalytic film, so that the catalytic film is formed on the substrate, the film comprising Ni in an oxidized state 2+ and Ni 3+ Non-stoichiometric and crystalline nickel oxide, and metal and / or metal oxide nanoparticles dispersed in the organic matrix.
[0072] In this embodiment, the metal salt and / or metal oxide is a metal other than nickel, which can be selected from Fe, Au, Ag, Ru, Ir, Pt, Pd, Re, Os, Rh, Mo, V and mixtures thereof, preferably one or more salts and / or one or more oxides of Fe, Au, Ag, Pt, Pd, Ru and Ir.
[0073] In this embodiment, a second cure is necessary to form metal nanoparticles and / or metal oxides in the organic matrix. In one embodiment, the second cure is performed at a temperature above 100° C., preferably above 200° C. Alternatively, curing can be performed with an ultraviolet lamp. With these treatments, metal nanoparticles and metal oxides are generated that bring new properties to the material.
[0074] In a third aspect, the present invention relates to use of the nickel oxide catalytic membrane according to the first aspect of the present invention as an electrode in water electrocatalysis.
[0075] Advantageously, the electrode has an overpotential of about 0.29V.
[0076] In a different embodiment, the present invention also relates to the use of the nickel oxide catalytic film according to the first aspect of the present invention as a photocatalytic electrode.
[0077] Advantageously, with the catalytic membrane of the present invention, reactive oxygen species (ROS) such as hydroxyl radicals (·OH) or superoxide (·O2 - ), which have REDOX properties for decomposing pollutants in water and atmosphere.
[0078] The authors of the present invention have been able to demonstrate that the organic portion that remains after the curing process, mainly due to the fact that lower temperatures are used, participates in the formation of pores that allow water penetration and therefore increases the contact with the catalyst and, therefore, improves the catalytic properties of the catalytic membrane defined in the present invention.
[0079] In contrast, in the prior art, curing is usually carried out at elevated temperatures to remove organic components so that the catalyst consists only of inorganic parts. Although in very thick films of the micrometer scale, many pores are generated when they are heated, in thin films of a few micrometers or nanometers, there is not enough space and it is compacted very quickly due to the generation of gaps. In addition, in the prior art, in order to obtain better compaction, high temperatures are preferred, considering that such compaction improves the catalytic properties and increases the stability of the catalyst.
[0080] Unexpectedly, the authors of the present invention have found that at lower temperatures, membranes are obtained with organic material in the middle of the pores; these pores allow water to flow between them. Thus, contrary to expectations, at lower temperatures, the catalytic membranes exhibit better catalytic properties while maintaining appropriate stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0081] For a better understanding of what has been said, some drawings are attached in which, schematically and purely by way of non-limiting example, practical implementations are represented.
[0082] Figure 1 Graphs showing the UV-visible absorbance of catalytic films obtained according to Example 1 at different aging times and a constant temperature of 50° C. in steps i)-c) for 0.9 M Ni(AcO) 2 solution in methoxyethanol.
[0083] Figure 2 Graph showing the UV-visible transmission spectra of catalytic films obtained according to Example 2 for different curing temperatures in steps iii) to e).
[0084] Figure 3 Graphs showing X-ray diffraction spectra of catalytic films obtained according to Example 2 for different curing temperatures in steps iii) to e).
[0085] Figure 4 Transmission electron microscope (TEM) images of the catalytic film obtained according to Example 2 and cured at a temperature of 100° C. compared to that cured at a temperature of 500° C. in steps iii)-e) are shown.
[0086] Figure 5 A graph showing the hydrolysis of water using a catalytic film obtained at a curing temperature of 100° C. according to Example 2 of the present invention.
[0087] Figure 6 The prior art oxides are shown to react at 10 mA cm in 1 M NaOH. -2Bar graph of overpotentials (V) under , described by McCrory et al. in "Benchmarking Heterogeneous Electrocatalysts for the Oxygen Evolution Reaction" in J. Am. Chem. Soc. 2013, 135, 16977-16987. DETAILED DESCRIPTION
[0088] Preferred embodiments for carrying out the invention are described below.
[0089] Example 1
[0090] Initially, a NiOx precursor solution was prepared. A 0.9 M solution of nickel acetate tetrahydrate (2.2 g) in methoxyethanol (V = 10 mL) was prepared, to which 0.04 mL of MEA was added. The mixture was stirred by dissolving a portion of the Ni(AcO)2. The mixture was then heated in a constant temperature bath at 30-70°C for 5-60 min. After 5 min, all the Ni(AcO)2 was dissolved. The aging step was followed by UV-VIS spectroscopy (see Figure 1 ).
[0091] Figure 1 Shown is a narrow band of UV absorbance at 397nm, and another wide band with a shoulder at 754nm visible at 670nm.After aging for 10 minutes, the band becomes stronger, and slightly moves to IR 400, 679 and 755nm respectively.Along with the increase of reaction time, the wavelength of the band does not change, but their intensity slightly increases when up to 60min, and now it is considered that the reaction is complete, because no intensity change is observed in up to 180min.After 180min, it is observed that owing to the formation of a translucent turquoise gel, the solution is no longer crystalline and transparent.This change is attributed to the hydrolysis and polycondensation of the nickel complex, resulting in the formation of acetate oxyhydroxides (acetate oxy-hydroxides) and methoxy ethoxide nickel (Ni (OH) 2, NiOOH) with a size exceeding 100nm and the gelation of undesirable solution.
[0092] Example 2
[0093] From the data extracted from the absorbance spectrum of Example 1, a 0.45 M Ni(AcO)2 solution aged at 70°C for 60 min was used as the NiOx precursor solution. The NiOx thin film was continuously deposited on the glass substrate by spin coating at a speed of 2,000 rpm for 20 s. Figure 2 Shown are the transmittance curves for different curing temperatures carried out over a period of 20 min at that temperature.
[0094] NiOx layer formation was followed by UV-Vis spectroscopy (see Figure 2 ). The presence of non-stoichiometric NiOx is confirmed by visible absorption between 900 and 350 nm. The drop in transmittance from 350 nm is due to the fact that the glass is not transparent to UV. It should be noted that stoichiometric NiO (Ni(II)) is a broadband semiconductor that does not absorb light in the visible spectrum, so the radiation absorption is due to the presence of part of the Ni in the form of Ni(III), which does absorb visible light. As the curing temperature increases from 50°C to 500°C (see Figure 2 ), the visible light absorption increases due to the formation of more Ni(III); as the temperature increases, solvent evaporation and acetate and methoxyethanol salt and MEA decomposition occur, generating NiOx with a larger relative amount of Ni(III). An inflection point is observed at curing temperatures above 200°C, where the transmittance at 550nm changes from 91% at 50°C to 80% at 200°C. From 200°C onwards, the change is significantly smaller.
[0095] test
[0096] In order to determine the crystallinity of the non-stoichiometric nickel oxide formed in the catalytic film, X-ray diffraction measurements were performed at different curing temperatures (see Figure 3 ).
[0097] It was observed that NiOx showed no diffraction peaks at different curing temperatures ranging from 50°C to 500°C, even at temperatures as high as 500°C. All observed peaks belong to silicon, which is the substrate used for the measurements. The absence of characteristic NiO, NiOOH or Ni(OH)2 peaks confirms that the NiOx film is formed by nanoscale crystalline domains, i.e., nanocrystals of very small size.
[0098] To confirm the presence of organic moieties after the curing step, images were taken using a transmission electron microscope (TEM) (see Figure 4 ).exist Figure 4 In the figure, the differences obtained between cured films from solutions with the same composition (e.g. a cured film at 100°C versus another cured film at 500°C) are shown. With the 500°C film, a very compact material with a thickness of about 25 nanometers was obtained. Surprisingly, the film cured at 100°C obtained a thickness of 100 nanometers with separation between particles. Contrary to expectations, the material shows better catalytic properties and adequate stability at lower temperatures.
[0099] The catalytic properties of the obtained catalytic membrane were then tested. The most representative measure of catalytic activity is the 10 mA / cm 2The overpotential required for the current density of water electrolysis. The overpotential is defined as the excess energy that must be applied for a reaction to occur, i.e., the activation energy. Generally speaking, all chemical reactions have an activation energy. Catalysts reduce the activation energy. In terms of electrochemistry, the activation energy can be equivalent to the overpotential to some extent. Therefore, we proceed to examine the overpotential required for water electrolysis using an electrode formed of a nickel sheet with a catalytic film. The overpotential obtained is about 0.29 V (290 mV) (see Figure 5 ), which shows an improvement over the overpotential measured with reference materials such as Ir and Ru oxides (see Figure 6 ), where in particular IrOx (non-stoichiometric iridium oxide) shows an overpotential of 0.33 V. Finally, a small peak of about 100 mV ( Figure 5 ) demonstrated the formation of Ni(III) oxide and, therefore, the conversion of part of Ni(II) from the Ni(II) state to Ni(III).
Claims
1. A nickel oxide catalytic film, characterized in that: It consists of oxidized Ni dispersed in an organic matrix. 2+ and Ni 3+ The catalytic film is supported on a substrate, wherein the organic matrix is formed by at least one organic compound selected from the group consisting of alkoxides, acetates, amines and / or derivatives of any one of them, wherein the organic matrix accounts for at least 10% by weight of the total weight of the catalytic film, The catalytic film is obtained by the following method, wherein the method is carried out on a substrate in a wet process as follows: i) preparing a nickel oxide precursor solution; ii) depositing the prepared solution on the substrate; iii) curing the solution deposited on the substrate to obtain the nickel oxide catalytic film; Characterized in that it comprises: In step i) a)-selecting an organic counter ion nickel salt; b) - dissolving the salt in a non-aqueous solvent of glycol ethers, glycol ether acetates and derivatives thereof in the presence of an amino alcohol chelating agent to obtain a solution of the nickel salt; c) - heating the solution to a temperature between 20 and 200° C. and maintaining the solution at a constant temperature for a certain period of time under stirring to obtain an aged solution; In step ii) d) - depositing the aged solution on the substrate by conventional wet deposition techniques to obtain a wet film; and In step iii) e) - curing said aged solution deposited on said substrate at a temperature between room temperature and 200° C., The catalytic film is formed on the substrate.
2. The catalytic membrane according to claim 1, wherein: The catalytic film has a thickness between 20-600 nm.
3. The catalytic membrane according to claim 1, wherein: The catalytic film has a thickness between 50-300 nm.
4. The catalytic membrane according to claim 1, wherein: The catalytic membrane is formed of one or more layers, each layer forming the catalytic membrane supported on the substrate.
5. The catalytic membrane according to claim 1, wherein: The catalytic film further includes metal nanoparticles and / or metal oxide nanoparticles dispersed in the organic matrix.
6. The catalytic membrane according to claim 1, wherein: The substrate is selected from insulating materials, conductive materials or electrical semiconductor materials.
7. The catalytic membrane according to claim 1, wherein: The substrate is selected from flexible, rigid or semi-rigid materials.
8. The catalytic membrane according to claim 1, wherein: The catalytic membrane supported on the substrate is an electrode.
9. A method for obtaining a catalytic membrane as defined in any one of claims 1 to 8, wherein: The method is carried out wet on a substrate as follows: i) preparing a nickel oxide precursor solution; ii) depositing the prepared solution on the substrate; iii) curing the solution deposited on the substrate to obtain the nickel oxide catalytic film; Characterized in that it comprises: In step i) a)-selecting an organic counter ion nickel salt; b) - dissolving the salt in a non-aqueous solvent of glycol ethers, glycol ether acetates and derivatives thereof in the presence of an amino alcohol chelating agent to obtain a solution of the nickel salt; c) - heating the solution to a temperature between 20 and 200° C. and maintaining the solution at a constant temperature for a certain period of time under stirring to obtain an aged solution; In step ii) d) - depositing the aged solution on the substrate by conventional wet deposition techniques to obtain a wet film; and In step iii) e) - curing said aged solution deposited on said substrate at a temperature between room temperature and 200° C., The catalytic film is formed on the substrate, wherein the catalytic film includes Ni in an oxidized state dispersed in the organic matrix. 2+ and Ni 3+ The non-stoichiometric and crystalline nickel oxide film.
10. The method according to claim 9, wherein: In steps i)-c), the solution is heated to a temperature between 50-100°C.
11. The method according to claim 9, wherein: In steps i)-c), the solution is heated to a temperature between 40-80°C.
12. The method according to claim 9, wherein: In steps iii)-e), curing of the aged solution deposited on the substrate is carried out at a temperature between room temperature and 100°C.
13. The method according to claim 9, wherein: In steps i)-c), the aging solution has a viscosity between 1.5 and 1,000 mPa·s.
14. The method according to claim 9, wherein: The organic counter ion is selected from one of the following: acetate, formate, oxalate, carbonate, octanoic acid glycolate, terephthalate, acetylacetonate, hexafluoroacetylacetonatoethylhexanoate, methoxyethanol, and sulfamate.
15. The method according to claim 9, wherein: In steps i)-b), the concentration of the nickel salt in the solution is equal to or greater than 0.05M.
16. The method according to claim 9, wherein: In steps i)-b), the non-aqueous solvent of the glycol ether is selected from 2-methoxyethanol, 2-ethoxyethanol, 2-butoxyethanol, 2-(2-ethoxy-ethoxy)ethanol, 2-propoxyethanol, 2-isopropoxyethanol, 2-benzyloxyethanol, 2-(2-methoxyethoxy)ethanol, 2-(2-butoxyethoxy)ethanol and derivatives or mixtures thereof.
17. The method according to claim 9, wherein: In steps i)-b), the amino alcohol chelating agent is selected from monoethanolamine, diethanolamine, triethanolamine and derivatives or mixtures thereof.
18. The method according to claim 9, further comprising: In steps i)-b) - Adding a previously prepared solution of one or more metal salts and / or metal oxides to the nickel salt solution.
19. The method according to claim 18, wherein: The metal salt and / or metal oxide is not nickel and is selected from the group consisting of salts and / or oxides of Au, Ag, Ru, Ir, Pt, Pd, Re, Os, Rh, Mo, V, Co, Fe and mixtures thereof.
20. Use of the nickel oxide catalytic membrane as defined in any one of claims 1 to 8 as an electrode in water electrocatalysis.
21. The use according to claim 20, wherein The electrode had an overpotential of 0.29V.
22. Use of the nickel oxide catalytic film as defined in any one of claims 1 to 8 as a photocatalytic electrode.
Citation Information
Patent Citations
Conductive paste and method for manufacturing composite nickel fine particle used therefor
JP2015049973A
Electrocatalytic materials and methods for manufacturing same
CN103974769A
Copper ion-doped nickel oxide colloidal nano-crystal preparation method and product thereof, and applications of copper ion-doped nickel oxide colloidal nano-crystal
CN106966441A
The Electrode comprising porous nickel oxide thin layer, preparation method and use in electrochromic device and lithium battery therof
KR1020100033777A